A gaming-based system for stroke patients physical rehabilitation - Abd Latif, Muhammad Hafiz; Md. Yusof, Hazlina; Sidek, Shahrul Na'im; Shikhraji, M.S.; Safie, M.H (2014)
The goals of rehabilitation are to improve function and gain as much independence as possible. As stroke attacks effect differs from person to person the type of rehabilitation would be unique. This paper looks into both independent physical and recreational therapy for a stroke patient using gaming based system, focusing on the Kinect sensor. The focus here is to investigate on how the gaming based system is able to reduce a patient dependability on the physiotherapist and increase their motivation and enthusiasm to continue their rehabilitation routine. By introducing gaming based rehabilitation, home therapy can be done in much pleasant way. Staying in home is less troublesome to the patient and therefore more conducive to a successful recovery. This paper concentrate on preliminary development of rehabilitation assisted game for arm area based on Kinect sensor.